Popularity As A Mediator Between Perceived Value, Unique Design, and Balinese Women’s Jewelry Preferences - Adinda Ayu Lestari Ningsih; Made Setini; Ni Made Wahyuni (International Journal of Islamic Business and Management Review, 2026)
The increasing use of imitation jewelry among Balinese women during traditional ceremonies reflects shifting consumer preferences influenced by economic considerations and aesthetic trends. This study examines the mediating role of popularity in the relationship between perceived value, design uniqueness, and consumer preferences for imitation jewelry. A quantitative approach was employed using a survey of 119 Balinese women who have used imitation jewelry in traditional activities. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived value and design uniqueness significantly influence consumer preferences and product popularity. Popularity also has a significant effect on consumer preferences and partially mediates the relationships between perceived value, design uniqueness, and preferences. Among the predictors, design uniqueness demonstrates the strongest direct effect on preferences. These findings highlight the importance of integrating cultural aesthetics, perceived value, and social influence strategies to enhance market acceptance of imitation jewelry in Bali. The study contributes to the literature on consumption value theory by incorporating popularity as a social mediating mechanism in cultural product consumption.